Pendidikan : Peluang Pengembangan Inovasi Kurikulum Masa Depan untuk Meningkatkan Mutu Pendidikan Nasional - Yassaro, Fierly Sabila (Maliki Interdisciplinary Journal, 2025)
The curriculum is an educational system that must develop according to the times. Current curriculum development has been integrated with technology. This is part of educational innovation, but the development of the curriculum does not escape the obstacles faced. Therefore, the curriculum development team must be applied in facing various challenges that will be carried out in curriculum development. Educational innovation is part of curriculum development. Educational innovation is carried out in order to create significant changes in educational orientation. So as to improve the quality of national education. Educational innovation is a necessity carried out by teachers and authorities, in order to form active, skilled, creative, collaborative, critical thinking students. Of course, through the learning process that has met the SNP (National Education Standards).